Limited utility of structural MRI to identify the epileptogenic zone in young children with tuberous sclerosis. Issue 5 (21st June 2022) - Nijman, Maaike; Yang, Edward; Jaimes, Camilo; Prohl, Anna K.; Sahin, Mustafa; Krueger, Darcy A.; Wu, Joyce Y.; Northrup, Hope; Stone, Scellig S.D.; Madsen, Joseph R.; Fallah, Aria; Blount, Jeffrey P.; et al.
Abstract: Background and Purpose: The success of epilepsy surgery in children with tuberous sclerosis complex (TSC) hinges on identification of the epileptogenic zone (EZ). We studied structural MRI markers of epileptogenic lesions in young children with TSC. Methods: We included 26 children with TSC who underwent epilepsy surgery before the age of 3 years at five sites, with 12 months or more follow‐up. Two neuroradiologists, blinded to surgical outcome data, reviewed 10 candidate lesions on preoperative MRI for characteristics of the tuber (large affected area, calcification, cyst‐like properties) and of focal cortical dysplasia (FCD) features (cortical malformation, gray‐white matter junction blurring, transmantle sign). They selected lesions suspect for the EZ based on structural MRI, and reselected after unblinding to seizure onset location on electroencephalography (EEG). Results: None of the tuber characteristics and FCD features were distinctive for the EZ, indicated by resected lesions in seizure‐free children. With structural MRI alone, the EZ was identified out of 10 lesions in 31%, and with addition of EEG data, this increased to 48%. However, rates of identification of resected lesions in non‐seizure‐free children were similar. Across 251 lesions, interrater agreement was moderate for large size ( κ  = .60), and fair ( κ  = .24) for all other features. Conclusions: In young children with TSC, the utility of structural MRI features is limited in the identification of the epileptogenic tuber, but improves when combined with EEG data.